PEMIMPIN SEBAGAI PENGGERAK MOTIVASI - Deta Putra Halawa; Khairani Amalia Simbolon; Sella Tusifa Adha; Apriyanto Zebua; Anggi Syahputra Sitorus; Rudi Syafrizal; M. Heriyanto; M. Diaz Bachtiar Nst; Erwin Syahputra (Nusantara Hasana Journal, 2022)
Leadership is closely related to a person's skills, abilities and knowledge in terms of influencing others to do something that is the desire and goal of a leader. A leader must have different types or traits, so with the typology of leadership, each type or nature of each leader can be grouped in order to create harmony between the leader's relationship with its members. In terms of motivation, the leader must have his own way or method in influencing his subordinates with the aim of improving the performance of responsible subordinates.